70.8k views
3 votes
Mia says that when you rearrange 3a - p = m to make a the subject of the formula you get:

a = m - p / 3
Mia is wrong. Explain and show her how to do the
question correctly.​

Mia says that when you rearrange 3a - p = m to make a the subject of the formula you-example-1
User DrPatience
by
6.7k points

2 Answers

3 votes

Answer:

see explanation

Explanation:

Mia is wrong in that she has subtracted p from both sides instead of adding p to both sides.

Given

3a - p = m ( add p to both sides )

3a = m + p ( isolate a by dividing both sides by 3 )

a =
(m+p)/(3)

User IBPX
by
5.9k points
4 votes

Answer:


a =(m+p)/(3)

Explanation:


3a - p = m

→ First plus p to both sides to isolate 3a


3a = m+p

→ Divide both sides by 3 to isolate a


a =(m+p)/(3)

User Rahim Khoja
by
5.6k points